Comparative Evaluation of Weight Variation and Mechanical Properties of Thermoplastic Materials Post Salivary Storage - Juvvadi, Shubhaker Rao; Himabindu, Himabindu; Gupta, Shivangi; Raghav, Pradeep; Reddy, Munish; Chauhan, Ashish (Journal of Neonatal Surgery, 2025)
The increasing demand for clear aligner treatments has highlighted the importance of metal-free thermoplastic materials in orthodontics. Materials such as Erkodur, Duran+, Imprelon, CA Pro+, Monoflex, and Leone are commonly used for fabricating these aligners. A study was conducted to evaluate the effect of storage in artificial saliva on the weight variation of specimens with different thicknesses (0.5, 0.6, 0.75, and 1 mm). The results indicated that immersion in artificial saliva leads to an increase in weight due to water absorption, which can affect the mechanical properties and fit of the aligners.​ Thermoplastic materials like PETG and TPU are known to absorb water when exposed to saliva, leading to dimensional changes and potential alterations in mechanical properties. For instance, a study found that TPU exhibited higher water absorption compared to PETG, with TPU showing a 1.45% weight increase after one week of water storage, while PETG showed a 0.84% increase . These changes can impact the force exerted by the aligners, potentially affecting treatment outcomes.​ ​In conclusion, while metal-free thermoplastic materials are essential in clear aligner therapy, their interaction with artificial saliva can lead to weight gain due to water absorption. This underscores the need for careful selection and testing of materials to ensure the effectiveness and longevity of orthodontic treatments.​